FACTORS INFLUENCING THE NON-USE AND ABANDONMENT OF ASSISTIVE TECHNOLOGY - FACTORS INFLUENCING THE NON-USE AND ABANDONMENT OF ASSISTIVE TECHNOLOGY (Research in Education and Rehabilitation, 2024)
ssistive technology is recognised as a necessary tool to improve the quality of life of people with disabilities. The use of assistive technology and the quality of related services varies from country to country. However, in most countries, there are some factors that influence the non-use or abandonment of assistive technology.This paper aim is to present the results of studies published in the period between 2015 and 2023 on the factors of non-use and/or abandonment of AT published in the articles cited in the Web of Science database. It also presents some results of three studies conducted in Croatia.The results show that difficulties in not using and abandonment AT appear in different social and cultural settings. Some of the most common factors identified were the health condition of the user, problems with use, inappropriate AT, lack of training of users and experts, lack of support, non-involvement of users in the AT design, etc.The non-use and abandonment of AT can harm the quality of life of people with disabilities. Many factors can influence AT abandonment. It is necessary to determine which factors influence the non-use and refusal to use assistive devices and which types of AT are most frequently not used. Understanding these factors is the first step in reducing the problem.